The Effects of Macroeconomic Variables on Stock Market Returns in Developing Markets: The Case of Indonesia - Sunarso, Nydia Angelina (2015)
This study analyses the relationship between Jakarta Stock Exchange All Share Indexes, a proxy for Indonesian stock returns, and six macroeconomic variables by carrying out the Ordinary Least Squares Method – Multivariate Regression Models for the period of 184 months from January 2000 to April 2015. The six macroeconomic variables used are the lagged changes of stock returns, the lagged changes of exchange rates, the lagged inflation rates, the lagged changes of crude oil prices, the lagged changes of industrial production indexes, and the lagged short-term interest rates. After exercising two different regression models, it is found that out of six employed macroeconomic variables, there are only three variables that have a significant impact on stock returns. They are the lagged changes of stock returns, the lagged changes of exchange rates, and the lagged changes of industrial production indexes. The lagged changes of stock returns and the lagged changes of exchange rates are shown to have a positive relationship with the changes of stock returns that are significant at the 99% significance level. On the other hand, the lagged changes of industrial production indexes and the changes of stock returns are found to be significantly and negatively correlated at the 95% confidence level. The result also suggests that Indonesian stock market possess the weak form market efficiency since its lagged stock returns can be used to explain almost 50% of the upcoming stock return. However, in general, it is discovered that Indonesian stock market is not efficient because it fails to directly respond to any movements of its macroeconomic variables. Instead, its stock returns react well to the macroeconomic variables’ lagged information.